N.F.S. Grundtvig og kærligheden til næsten - Nyborg, Ole (Dansk Teologisk Tidsskrift, 2012)
In this paper the conception of Christian love to neighbours and fellow human beings is analyzed within the sermons of the Danish theologian N.F.S. Grundtvig (1783-1872). In his sermons Grundtvig persistently expresses the importance of the value of fatherliness. The Christian person should thus act in a strongly fatherly way towards his neighbour. Grundtvig criticizes popular ideas of his own time of the nature and essence of Christian neighbour love, and he distinguishes sharply between a true and a false sort of Christian love. According to the sermons of Grundtvig, only a responsible and fatherly, or even patriarchal, way of loving can be a true form of Christian love. These findings break with quite a few common assumptions in the research literature.